Identifying and Spurring High-Growth Entrepreneurship : Experimental Evidence from a Business Plan Competition - McKenzie, David (American Economic Association, 2017)
Almost all firms in developing countries have fewer than ten workers, with a modal size of one. Are there potential high-growth entrepreneurs, and can public policy help identify them and facilitate their growth? A large-scale national business plan competition in Nigeria provides evidence on these questions. Random assignment of US$34 million in grants provided each winner with approximately US$50,000. Surveys tracking applicants over five years show that winning leads to greater firm entry, more survival, higher profits and sales, and higher employment, including increases of over 20 percentage points in the likelihood of a firm having ten or more workers.